Pengaruh Dana Bantuan Operasional Sekolah dan Sarana Prasarana Sekolah Terhadap Kualitas Pendidikan SMP Negeri 1 Jatinegara Kabupaten Tegal - Daffa Putra Suasra; Jonet Ariyanto Nugroho; Salman Afarisy Totalia (Journal on Education, 2023)
The purpose of this study was to determine the effect of school operational assistance funds (BOS) and school infrastructure on the quality of education at SMP Negeri 1 Jatinegara. The subjects of this study were 597 students in grades 7, 8 and 9 of SMP Negeri 1 Jatinegara for the 2022/2023 academic year, with a sample of 238 students. The research method in this study is a quantitative research method, and sampling use proportional stratified random sampling. Data collection techniques in this study use a questionnaire. This study uses multiple linear regression analysis. The conclution on that BOS funds had no effect on the quality of education at SMP Negeri 1 Jantinegara. School infrastructure has a positive effect on the quality or quality of education at Jatinegara 1 Public Middle School, which can be seen from the t table which is smaller than the t count, namely 1.651 < 8.050. Furthermore, school operational assistance funds and school infrastructure simultaneously have a positive influence on the quality of education at SMP Negeri 1 Jatinegara as show by the F table value which is smaller than the calculate F value, namely 3.034 < 46.255.